Lactation in Farm Animals Biology, Physiological Basis, Nutritional Requirements, and Modelization - M'Hamdi, Naceur (Veterinary Medicine and Science, 2020)
Greater knowledge of lactation allows us to alter environmental, nutritional, and milking procedures, or general management to maximize production. This book, focusing on lactation in farm animals (biology, physiological basis, nutritional requirements, and modelization), presents invited papers from internationally recognized scientists. This volume contains seven chapters covering the key topics related to milk production and lactation biology and physiology. The authors show that animals raised on a well-controlled nutrition regimen may have significant enhancement of succeeding lactations. Furthermore, the usefulness of a milk yield prediction system depends upon how accurately it can predict daily milking patterns and its ability to adjust to factors affecting supply. Milk yield prediction models have proven helpful for genetic analysis and for bio-economic modeling. On the whole, this book serves as an inspirational basis for both scientists and farmers.